2014
DOI: 10.1161/jaha.114.001059
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness Level and Off‐Hour Admission Affect Discharge Outcome of Acute Stroke Patients: A J‐ASPECT Study

Abstract: BackgroundPoor outcomes have been reported for stroke patients admitted outside of regular working hours. However, few studies have adjusted for case severity. In this nationwide assessment, we examined relationships between hospital admission time and disabilities at discharge while considering case severity.Methods and ResultsWe analyzed 35 685 acute stroke patients admitted to 262 hospitals between April 2010 and May 2011 for ischemic stroke (IS), intracerebral hemorrhage (ICH), or subarachnoid hemorrhage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
(74 reference statements)
1
20
0
Order By: Relevance
“…[2,12,2934] However, the effect of weekend or off-hour admission on mortality has been negated after adjustment for stroke severity as assessed by using a stroke scale or a similar proxy, [4,9,10,28,35,36] as seen in the present study. The present analysis also found that the effect of brain surgery on mortality turned from harmful to null after adjustment for stroke severity.…”
Section: Discussionmentioning
confidence: 54%
“…[2,12,2934] However, the effect of weekend or off-hour admission on mortality has been negated after adjustment for stroke severity as assessed by using a stroke scale or a similar proxy, [4,9,10,28,35,36] as seen in the present study. The present analysis also found that the effect of brain surgery on mortality turned from harmful to null after adjustment for stroke severity.…”
Section: Discussionmentioning
confidence: 54%
“…Using this database, we have previously reported the discharge outcomes of cerebrovascular disease patients in a nationwide retrospective analysis (the J-ASPECT study). 1113) In this study, we collected and analyzed all the DPC data for patients treated in 370 core and branch hospitals from a total of 847 hospitals participating in the Japan Neurosurgical Society training program. Brain tumor patients are treated in neurosurgical hospitals in Japan, and this treatment includes CTX and RT.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of admission serum glucose might be the critical component which leads to a higher discrimination power of predicting the unfavorable outcome of ICH patients using ICH‐FOS score than the max‐ICH score. The level of consciousness was reported to be one of the most significant factors of poor outcome of ICH patients . The superior performance of Essen‐ICH score in recognizing unfavorable long‐term outcome of ICH patients might due to highlighting the importance of consciousness level.…”
Section: Discussionmentioning
confidence: 99%